Based on Slrj.chat.md; inspired by a conversation with aljce
You are a knowledgeable programming languages assistant. You help the user analyze a new programming language.
Aljc is a new programming language. The grammar of Aljc expressions is defined as follows, where x
is any Aljc expression and A
, B
, and C
are atomic values.
x ::= A | B | C | (x x)
The small-step semantics of Aljc are defined by the following rewrite rules, where x -> y
is the relation that x
steps to y
, for some Aljc expressions x
and y
.
(A x) -> x
((B x) y) -> ((y x) x)
(((C x) y) z) -> ((z x) y)
An Aljc expression is evaluated by applying rewrite rules from Aljc's semantics until no more rewrite rules can be applied. The following are some examples of evaluations of Aljc expressions:
(A B)
evaluates toA
((B A) C)
evaluates to((C A) A)
(((C A) A) B)
evaluates toA
What does (((C A) A) B)
evaluate to? Show the evaluation steps.
Let's evaluate the Aljc expression (((C A) A) B)
step by step using the provided rewrite rules.
Given expression: (((C A) A) B)
Step 1: Apply the rule (((C x) y) z) -> ((z x) y)
with x = A
, y = A
, and z = B
.
(((C A) A) B) -> ((B A) A)
Step 2: Apply the rule ((B x) y) -> ((y x) x)
with x = A
and y = A
.
((B A) A) -> ((A A) A)
Step 3: Apply the rule (A x) -> x
with x = (A A)
.
((A A) A) -> (A A)
Step 4: Apply the rule (A x) -> x
with x = A
.
(A A) -> A
No more rewrite rules can be applied, so the evaluation is complete.
Therefore, the Aljc expression (((C A) A) B)
evaluates to A
.
It doesnt the full evaluation correctly!
User
... same as chat1.md except for the last line ...
What does
(((C (B C)) (A A)) B)
evaluate to? Show the evaluation steps.Assistant (Claude 3 Opus)
Great question! Let's evaluate the Aljc expression
(((C (B C)) (A A)) B)
step by step using the provided small-step semantics.Step 1:
(((C (B C)) (A A)) B)
We can apply the rewrite rule
(A x) -> x
to the subexpression(A A)
:(A A) -> A
Step 2:
(((C (B C)) A) B)
Now we can apply the rewrite rule
(((C x) y) z) -> ((z x) y)
to the entire expression:(((C (B C)) A) B) -> ((B (B C)) A)
Step 3:
((B (B C)) A)
We can apply the rewrite rule
((B x) y) -> ((y x) x)
to the expression:((B (B C)) A) -> ((A (B C)) (B C))
Step 4:
((A (B C)) (B C))
Finally, we can apply the rewrite rule
(A x) -> x
to the subexpression(A (B C))
:(A (B C)) -> (B C)
Step 5:
(B C)
No more rewrite rules can be applied, so the evaluation is complete.
Therefore, the Aljc expression
(((C (B C)) (A A)) B)
evaluates to(B C)
.Comment
It does a few steps correctly, but then kinda forgets where it was in the evaluation and pretends that a subexpression it just simplified,
(B C)
is actually the entire expression.